Institutional Evolution and Change: Environmentalism and the U.S. Chemical Industry - Hoffman, Andrew J. (Academy of Management Journal, 1999)
This study measured changes in the constituency of an organizational field centered around the issue of corporate environmentalism in the period 1960?93, correlating those changes with the institutions adapted by the U.S. chemical industry to interpret the issue. The article develops the ideas that fields form around issues, not markets or technologies; within fields, competing institutions may simultaneously exist; as institutions evolve, connections between their regulative, normative, and cognitive aspects arise; and field-level analyses can reveal the cultural and institutional origins of organizational impacts on the natural environment.